2019
DOI: 10.1093/milmed/usz335
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Automated Neurofeedback Therapy for Persistent Postconcussive Symptoms in a Military Clinical Setting: A Feasibility Study

Abstract: Introduction Neurofeedback therapy (NFT) has demonstrated effectiveness for reducing persistent symptoms following traumatic brain injury (TBI); however, its reliance on NFT experts for administration and high number of treatment sessions limits its use in military medicine. Here, we assess the feasibility of live Z-score training (LZT)—a variant of NFT that requires fewer treatment sessions and can be administered by nonexperts—for use in a military clinical setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Elbogen et al [14] ( n = 41), reported the number of participants who experienced different side effects such as headset discomfort ( n = 14), drowsiness ( n = 13), irritability ( n = 6), headache ( n = 3), dizziness ( n = 1), vibrating/buzzing ( n = 1), and muscle twitching ( n = 1). Finally, two (out of 38) of the participants in Hershaw et al [18] dropped out due to nausea and intensification of their pre‐existing headache, and two more were pulled out by the investigators due to an increase in their pre‐existing migraines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elbogen et al [14] ( n = 41), reported the number of participants who experienced different side effects such as headset discomfort ( n = 14), drowsiness ( n = 13), irritability ( n = 6), headache ( n = 3), dizziness ( n = 1), vibrating/buzzing ( n = 1), and muscle twitching ( n = 1). Finally, two (out of 38) of the participants in Hershaw et al [18] dropped out due to nausea and intensification of their pre‐existing headache, and two more were pulled out by the investigators due to an increase in their pre‐existing migraines.…”
Section: Resultsmentioning
confidence: 99%
“…The targeted frequency bands are extracted and processed in real time, then their calculated power is presented to the individual as a form of positive or negative reinforcement [11,17]. Examples of such reinforcement include advancement or setbacks in a video game, and positive/negative visual and auditory feedback [18,19]. Different EEG neurofeedback techniques train individuals with chronic pain to gain control over their abnormal brain activity, which ultimately leads to pain reduction [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Ayers (1989) was the first to report positive effects of NF on TBI-related symptoms, finding improvements in a number of postconcussive symptoms experienced by patients, including decreased energy, depression, irritability, photophobia, attention deficit, dizziness, headache, and short-term memory loss. The role of NF in improving cognitive, behavioral, and physical dysfunctions among patients with TBI has been confirmed in previous studies (Bennett et al, 2018;Brown et al, 2019;Gray, 2017;Gupta et al, 2020;Hershaw et al, 2020;Kaser, 2020;Koberda, 2015a).…”
Section: Introductionmentioning
confidence: 53%
“…Most of the neurofeedback studies have measured changes in pain immediately following neurofeedback [39,43,52,55,56]. Furthermore, pain reduction has been reported to be sustained even at follow up of 3-6 months after completion of neurofeedback training [28,36,41,[49][50][51]54]. However, these studies do not report whether the corresponding change in brain rhythm which were measured following completion of training were also sustained at long-term follow-up.…”
Section: Efficacy Of Neurofeedback In Management Of Chronic Painmentioning
confidence: 99%
“…It has been shown that neurofeedback not only leads to reduction in pain but leads to improvement in a number of pain associated symptoms such as depression [27,39,41,54,[57][58][59][60], anxiety [27,41,54,57,59], fatigue [27,29,41,49,51], and sleep [36,39,[49][50][51]57]. These symptoms have been known to co-exist with pain in chronic pain conditions and also known to exacerbate the individual's pain on a dayto-day basis [61][62][63].…”
Section: Efficacy Of Neurofeedback In Management Of Chronic Painmentioning
confidence: 99%